2014
DOI: 10.1182/blood-2014-01-549733
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of venous thromboembolism recurrence and bleeding among active cancer patients: a population-based cohort study

Abstract: Key Points• VTE recurrence risk in patients with cancer can be stratified by cancer type, stage, stage progression, and presence of leg paresis.• Patients with cancer at high VTE recurrence risk should be considered for secondary prophylaxis.Active cancer is the major predictor of venous thromboembolism (VTE) recurrence, but further stratification of recurrence risk is uncertain. In a population-based cohort study of all Olmsted County, Minnesota, residents with active cancer-related incident VTE during the 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 40 publications
13
140
2
2
Order By: Relevance
“…1,2,5,[19][20][21] For this study, we restricted our analyses to residents with incident or recurrent leg DVT alone (including isolated anterior and posterior tibial and peroneal [calf] DVT but excluding isolated gastrocnemius or soleal vein thrombosis) or PE with or without DVT (excluding isolated subsegmental PE) over the 6-year period 2005-2010; 98% of events were objectively diagnosed, and the remainder were clinically diagnosed events treated with anticoagulants. Olmsted County residents with a first VTE while a nonresident and a recurrence while a resident were also included (see supplemental Data).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,5,[19][20][21] For this study, we restricted our analyses to residents with incident or recurrent leg DVT alone (including isolated anterior and posterior tibial and peroneal [calf] DVT but excluding isolated gastrocnemius or soleal vein thrombosis) or PE with or without DVT (excluding isolated subsegmental PE) over the 6-year period 2005-2010; 98% of events were objectively diagnosed, and the remainder were clinically diagnosed events treated with anticoagulants. Olmsted County residents with a first VTE while a nonresident and a recurrence while a resident were also included (see supplemental Data).…”
Section: Methodsmentioning
confidence: 99%
“…Recurrent VTE was defined as thrombosis of a venous site that was either previously uninvolved or had interval documentation of thrombus resolution. 5,20,21 For deceased patients, all death certificates and autopsy reports were reviewed regardless of the location at death. The study was approved by the Mayo Clinic and Olmsted Medical Center institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on expert discussions and widespread clinical practice, anticoagulation treatment after a 6-month treatment period is usually guided by a thorough assessment of the factors contributing directly to the risk of recurrent cancer-associated thrombosis (including the risk of cancer recurrence). Risk stratification based on the tumour type or biology; stage of disease; and patient comorbidities (hospitalization or immobilization, surgery, chemotherapy or radiation therapy, central venous catheter insertion, or localized tumour compression) is important 10 .…”
Section: Statementmentioning
confidence: 99%
“…Other studies have identified additional risk factors for recurrent VTE. For example, in the Olmstead County population based cohort study, cancer type, stage, stage progression, and leg paresis were significant risk factors,21 while elevated tissue factor, venous compression, and hepatobiliary cancer were identified as risk factors in the CATCH study 22. More studies are needed to delineate the most useful risk assessment tool to help clinicians to identify patients with high risk of recurrent VTE.…”
Section: Risk Factors Of Cancer‐associated Thrombosismentioning
confidence: 99%